Postoperative pain and analgesic consumption after endoscopic and microscopic ear procedures - Salzman, Richard; Bakaj, Tomas; Starek, Ivo (Biomedical papers, 2022)
Objective. Endoscopic ear surgery (EES) is considered a minimally invasive technique. It is hypothesized that patients after endoscopic procedures experience less pain and require fewer painkillers. Our aim was to compare patients' postoperative pain and need for analgesics in patients undergoing microscopic and endoscopic ear surgeries. Methods. a single-institution, prospective study included 92 patients undergoing ear procedures (48 cholesteatoma and 44 reconstructive);(43 endoscopic and 49 microscopic) during 1/2016-1/2018. The postoperative pain (visual analogue scale (VAS) 0-10) and painkillers consumption were recorded and compared in each subgroup. Results. VAS (P=0.02) and analgesics consumption (P=0.06) were lower after endoscopic ear surgeries. In the cholesteatoma group, 94% of endoscopic patients reported VAS 0-2 in contrast to 58 % of microscopic patients on day 1 (P=0.04). Similar tendencies were revealed in reconstructive cases, i.e. 92% compared to 73% (P>0.05). On day 1, 92% of endoscopic, and 77% of microscopic reconstruction patients received no painkillers group (P=0.06). In the cholesteatoma patients, 88% of endoscopic patients, 43% of microscopic patients using endaural approach, and 75% of microscopic patients using retroauricular approach, required no painkillers on the postoperative day 1 (P>0.05). Conclusions. Our study revealed that the EES is associated with less postoperative pain than the conventional microscopic ear surgery. It seems that it is rather the transmeatal approach, and not the endoscope itself that reduces postoperative pain. The removal of the same size cholesteatoma using endoscope (rather than using microscope) leads to less intensive postoperative pain. Consequently, it was not surprising that patients after endoscopic ear surgery very rarely took painkillers.
Keywords: life quality; pain measurement; pain; stapes surgery; transcanal endoscopic ear surgery; tympanoplasty